Non-alcoholic fatty liver disease in diabetes mellitus patients on chronic hemodialysis – A case series addressing cardiovascular and mortality risks - Stoica, Roxana Adriana; Tribus, Laura Carina; Marin, Raluca Ioana; David, Tara; Preda, Carmen Monica; Bica, Ioana Cristina; Serafinceanu, Cristian (Frontiers in Clinical Diabetes and Healthcare, 2023)
Non-alcoholic fatty liver disease (NAFLD) has an important role in the pathogenesis of cardiovascular diseases in the population with diabetes and it is highly prevalent in end-stage renal disease (ESRD) patients. This case series describes NAFLD associated factors and survival in type 2 diabetes patients (T2DM) who have ESRD treated with hemodialysis. NAFLD prevalence in patients with T2DM and ESRD is 69.2%. A high number of patients (15 out of 18) have obesity evaluated by calculating body mass index (BMI) and bioimpedance measurements. Patients with NAFLD have higher cardiovascular mortality risk, 13 of 18 patients were already diagnosed with coronary heart disease, 6 of 18 had cerebrovascular disease, and 6 of 18 had peripheral artery disease. Fourteen patients were treated with insulin, two patients with sitagliptin (renal adjusted dose of 25mg/day) and two patients with medical nutrition therapy, with an HbA1c ranging from 4.4 to 9.0%. After one-year follow-up 7 of 18 patients died, the causes having roughly equal proportions: myocardial infarction, SARS-CoV2 infection, and pulmonary edema. In conclusion, our population of type 2 diabetic patients with ESRD in hemodialysis had a prevalence of ultrasound-diagnosed NAFLD of 69.2%. Also, this population had a high death rate at one-year follow-up, cardiovascular causes being among the most common.